Peningkatkan Daya Saing Industri Rumah Tangga Melalui Program Pelatihan dan Pendampingan Keuangan Usaha di Desa Kindang - Anwar Anwar; Zainal Ruma; Nurman Nurman; Chalid Imran Musa; Khaidir Syahrul (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Kindang Village is one of the villages that has quite large potential for home industries, but still faces challenges in effective business financial management. This community service activity aims to increase the competitiveness of home industries through training and mentoring in sustainable business financial management. The implementation method includes socialization, simple financial management training, financial record keeping, and intensive mentoring for three months. The results of the activity show an increase in business actors' understanding of the importance of financial records and business planning, as well as changes in behavior in managing cash flow and determining product selling prices. This program has succeeded in building financial awareness and increasing the efficiency of business management, which has an impact on increasing the competitiveness of home industries in Kindang Village.